Red blood cell distribution width-to-albumin ratio and its association with age-related macular degeneration: a population-based cross-sectional study - An, Ning; Zeng, Bing; Liu, Ziling; Zhang, Chuanhe; Liao, Hongxia; Liu, Dongcheng; Qin, Bo (Frontiers in Medicine, 2025)
BackgroundAge-related macular degeneration (AMD) is a leading cause of central vision impairment in middle-aged and older individuals. There is substantial evidence that AMD is associated with inflammation. The study aimed to investigate the association between the inflammatory marker, red blood cell distribution width/albumin ratio (RAR), and AMD.MethodsOur study included 5,370 participants aged 40 years and older, using NHANES data from 2005 to 2008. Multivariable logistic regression analysis was conducted to examine the relationship between RAR and AMD in the study. Smooth curves and the piecewise linear regression model were used to determine whether the correlation was linear or non-linear. Additionally, subgroup analysis and interaction testing were performed.ResultsWe found a positive linear correlation between RAR and AMD, even after adjusting for covariates. Each unit increase in RAR corresponded to a 30% increase in the odds of AMD prevalence (OR = 1.3; 95% CI, 1.0–1.6). The odds of AMD prevalence were 1.7 times greater in the highest quintile (Q5) group than in the lowest quintile (Q1) group (OR = 1.7; 95% CI, 1.2–2.5). Higher RAR values, compared to lower values, were significantly associated with increased odds of AMD prevalence (p trend < 0.05). Subgroup analyses and interaction tests confirmed the stability of the findings.ConclusionThis study found that there is a positive linear correlation between RAR and the odds of AMD prevalence in United States adults. Further research is necessary to clarify the specific physiological mechanisms underlying the relationship between RAR and AMD.